Recovery Capital and Quality of Life in Stable Recovery From Addiction. (July 2019) - O'Sullivan, Deirdre; Xiao, Yi; Watts, Justin R.
Quality of life is becoming an increasingly important outcome measure in both relapse prevention research and rehabilitation counseling research. Recovery capital is a collection of the people and resources believed to contribute to long-term recovery from addiction. Recovery capital indicators were assessed along with quality of life in a national sample of peer support participants in stable recovery ( n = 76) to determine which recovery capital indicators relate to quality of life at this stage. Results reveal that relapse history, refusal self-efficacy, and self-stigma significantly explained about 23% of quality of life in our sample. A discussion of recovery stages and recovery capital is included, as well as implications for rehabilitation counseling practice and research.